Fiber grating based filter design and development - Peng, Qizhen. (2008)
Fiber Bragg grating(FBG)represents a key element in modules and subsystems for Wavelength Division Multiplexing(WDM)optical system. When used as a n optical filter,it provides many advantages compared with other competing technologies. These include low insertion loss, potentially low cost and highly flexible spectral characteristics.